Respuesta :
We start with writing the terms containing x and y together. We get 9x^2 + 36x + 4y^2 – 8y + 4 =0
=> 9(x^2 + 4x) + 4(y^2 – 2y) + 4 =0
Now complete the squares
=> 9(x^2 + 4x +4) +4(y^2 – 2y +1) = -4 + 36 + 4
divide both the sides by 36
=> (x^2 + 4x +4)/4 + (y^2 – 2y +1)/9 = 1
=> (x + 2)...
Answer:
[tex]\frac{(x-2)^{2}}{4} + \frac{y^{2}}{9} = 1[/tex]
Step-by-step explanation:
The standard form of the ellipse is determined by completing the squares and some algebraic handling:
[tex](3\cdot x)^{2} - 12\cdot(3\cdot x) + 36 +4\cdot y ^{2} - 36 = 0[/tex]
[tex](3\cdot x - 6)^{2} + 4\cdot y^{2} = 36[/tex]
[tex]9\cdot (x -2)^{2} + 4\cdot y^{2} = 36[/tex]
[tex]\frac{(x-2)^{2}}{4} + \frac{y^{2}}{9} = 1[/tex]